Factors influence brand loyalty towards Power Ficos company / Rozaireen Baharom and Juraiza Ezza Johari - Baharom, Rozaireen; Johari, Juraiza Ezza (2013)
The aim of this paper is to examine the Factors Influence of Brand Loyalty on Power Ficos Company. There are five factors are examined by the researcher. The factors are product quality, price, promotion, service quality and design. There are 135 questionnaires has been distributed in area of Duyong, Melaka. From the recent research, three out of five of independent have significant to the factors influence brand loyalty on Power Ficos Technologies Company. The variables are design, service quality and price. The main objective of the study are to identify the level of brand loyalty towards Power Ficos Company, to determine the relationship between the factors influence and brand loyalty towards Power Ficos Company, to determine the factor that mostly contributes brand loyalty towards Power Ficos Company and to provide suggestion and recommendation to improving the brand loyalty towards Power Ficos Company.